The Missing lnc(RNA) between the pancreatic β-cell and diabetes - Kameswaran, Vasumathi; Kaestner, Klaus H. (Frontiers in Genetics, 2014)
Diabetes mellitus represents a group of complex metabolic diseases that result in impaired glucose homeostasis, which includes destruction of β-cells or the failure of these insulin-secreting cells to compensate for increased metabolic demand. Despite a strong interest in characterizing the transcriptome of the different human islet cell types to understand the molecular basis of diabetes, very little attention has been paid to the role of long non-coding RNAs (lncRNAs) and their contribution to this disease. Here we summarize the growing evidence for the potential role of these lncRNAs in beta cell function and dysregulation in diabetes with a focus on imprinted genomic loci.